The Acquirements of the Students with Their Own Perspectives during the Preclinical Primary Care Experience - APAYDIN KAYA, MEMNUNE ÇİĞDEM; SARIKAYA, ÖZLEM (DUZCE UNIV, 2019)
Objective: The aim of this study is to evaluate the acquirements of the students during the preclinical Family Medicine experience with their own perspectives. Methods: The methodology of the study is qualitative. In the 2017-2018 education year, observation and experience reports of the 147 students at the end of the Primary Care Experience Program applied in 3rd class of Marmara University Medical School were evaluated in terms of structure and content. After that, thematic analysis was applied to 61 reports that met the expectations in terms of structure and content. Results: The acquirements of the students were classified as: Medical knowledge, Basic clinical skills, Attitudes and behaviors towards professionalism, Awareness of their own competences and boundaries, Recognition of family medicine and primary care practices and Associating medical education with the other components and contribution to learning. Conclusions: This research revealed that the primary care experience theme is a program that enables physician candidates to develop their attitudes and behaviors towards professionalism, to improve their medical knowledge and skills, as well as to be able to recognize their own competencies and boundaries. The program also allowed recognition of the discipline of the Family Medicine by the students.
Keywords: Primary Care; Medical Education; Qualitative Research; Family Medicine; MEDICAL-EDUCATION